A Stable Fluorine‐Containing Solid Electrolyte Interface toward Dendrite‐Free Lithium‐Metal Anode for Lithium‐Sulfur Batteries. Issue 8 (15th April 2021) - Chen, Yuchao; Mao, Yangyang; Hao, Xiaoqian; Cao, Yongan; Wang, Wenju
Abstract: Lithium‐sulfur (Li−S) batteries are considered to be a representative of the next generation of lithium‐ion batteries due to their high theoretical specific capacity (2600 Wh ⋅ Kg −1 ), and they have been extensively researched. However, the formation of lithium dendrites during the discharge process continuously consumes the electrolyte and the lithium anode, resulting in an increase in the cell's internal resistance and a capacity loss. Herein, we added an organic‐inorganic polymer hexafluoro‐cyclo‐triphosphazene (HFPP) to the electrolyte, which showed lower interfacial resistance and more effective lithium‐ion deposition. The lone‐pair electrons of the nitrogen atoms in HFPP promote the uniform diffusion of lithium ions and its 2D structure also enhances the mechanical stability of the solid electrolyte interphase (SEI) and inhibits the formation of lithium dendrites. Based on the regulating effect, the cells using HFPP as electrolyte additives showed an excellent discharge capacity of 1095 mAh ⋅ g −1 at 0.5 C and a reversible capacity of 763 mAh ⋅ g −1 after 200 cycles, indicating that HFPP is an effective additive for the protection of the lithium anode and cycling stability of Li−S batteries. Abstract : Li‐S Batteries : Hexafluoro‐cyclo‐triphosphazene (HFPP) has a stable structure and a relatively strong affinity for lithium. Cells using HFPP as an electrolyte additive showed an excellent discharge capacity of 1095 mAh ⋅ g −1 at 0.5 C and a reversible capacity of 763 mAh ⋅ g −1 after 200 cycles, indicating that HFPP is an effective additive for the protection of the lithium anode and cycling stability of Li−S batteries.